STUDENT’S ABILITY IN ENGLISH SPEAKING SKILL BY USING PICTURE (A COMPARATIVE STUDY BETWEEN MUHAMMADIYAH ISLAMIC SCHOOL AND SMAN 1 SIMEULUE TIMUR) - Indratmoko Ariwibowo (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2010)
This study is intended to figure out if there is a significant difference in English speaking ability between public school students and Islamic school students. The population of this study is the second year students of both SMAN 1 Simeulue Timur and Muhammadiyah Islamic School Simeulue Timur. The samples of this study were 20 students taken from two classes at SMAN 1 Simeulu Timur and 20 students taken from two classes at Muhammadiyah Islamic School Simeulue Timur. So, the total number of samples from the two schools was 40 students. In collecting the data, the writer gave a picture of 26th December 2004 tsunami in Aceh. The students were asked to describe the picture by their own words. In analyzing the data, the writer used t-test formula to see the significant difference between the students of the two schools in English speaking ability. The mean and standard deviation scores for Muhammadiyah Islamic School Simeulue Timur are 35.25 and 8.20. While the mean and mean and standard deviation scores for SMAN 1 Simeulue Timur are 39 and 8. The result of t-test of the two schools is 13.20. It is considered higher than t value on the table if significance at level 0.05 and 38 for the degree of the freedom which is stated 2.02. The writer concludes that the speaking ability between SMAN 1 Simeulue Timur and Muhammadiyah Islamic School Simeulue Timur is significantly different. Furthermore, the writer found that students of SMAN 1 Simeulue Timur are better in speaking ability than those of Muhammadiyah Islamic School Simeulue Timur. Therefore, the writer suggests that the teachers of boarding school should evaluate their teaching learning process and have more motivation to improve their student’s ability English speaking